2015
DOI: 10.1111/jsm.12762
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Numerous Vesical Magnetic Beads with a Self-Made Magnetic Sheath

Abstract: Introduction Sexual curiosity and the quest for sexual excitement are the most frequent reasons for patients to introduce foreign bodies into the urethra or the bladder. Imagination and surgical skill are essential for urologists to retrieve such vesical foreign bodies. Aim The aim of this study was to describe a novel method for retrieving vesical magnetic beads, which were inserted for autoeroticism by a male adolescent, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Several medical case reports highlight the morbidity associated with this practice, most commonly when the sounding device, where an object has been used, can no longer be retrieved by the participant and requires urological review, often as an emergency. Diagnosis can usually be achieved by a plain radiograph; however, ultrasonography and CT imaging have been used [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several medical case reports highlight the morbidity associated with this practice, most commonly when the sounding device, where an object has been used, can no longer be retrieved by the participant and requires urological review, often as an emergency. Diagnosis can usually be achieved by a plain radiograph; however, ultrasonography and CT imaging have been used [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen cases involving the insertion of magnetic beads into the urethra for the purpose of sexual stimulation have been reported since 2011 [9,1113,15] (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robey et al beschreven een percutane cystotomie bij een 12-jarige jongen, bij wie met een nefroscoop eenvoudig 27 magneetkralen werden verwijderd met een paktang [8]. Zeng et al beschreven een alternatieve techniek voor endoscopische extractie van de magneetkralen, waarbij ze één 3mm-magneetkraal stevig hadden gefixeerd in het uiteinde van een F9,5-ureterale access sheath [9]. De patiënt werd in steensnedeligging geopereerd onder algehele anesthesie.…”
Section: Discussieunclassified
“…3 Utilizing their magnetic properties has been documented as a successful tactic to removing magnets in the bladder and duodenum. Zeng et al 4 retrieved 125 magnetic beads in the bladder cystoscopically by using a home-made magnetic sheath (an ureteral access sheath with a magnetic bead on the tip), and another study 5 reported that a magnetic ball in a glove finger tied like a bag was inserted through the gastroscope to remove 18 magnetic beads in duodenum. However, the use of a transnasal ileus catheter has not been reported in this field.…”
mentioning
confidence: 99%